In vivo activities of ethanolic extract from endiandra kingiana (lauraceae) as potential anti-diabetic agents - Noriman, Ahmad Zakwan (2021)
Diabetes mellitus is one of the most prevalent diseases in the worldwide population. The impairment in insulin secretion, insulin action or both has led to the hyperglycaemic condition. In 2019, 4.2 million deaths were reported due to diabetes mellitus. Uncontrolled hyperglycaemia condition leads to secondary complications such as retinopathy, nephropathy, cardiomyopathy, and limb amputation. Thus, one of the plants found in Malaysia, known as Endiandra kingiana (Pokok Medang) was evaluated. It has in vitro α-glucosidase inhibitory effect but lacking evidence in in vivo antidiabetic properties. Thus, there is merit to evaluate the antidiabetic effects of oral crude bark E. kingiana ethanolic extract (EKEE) on Type 2 diabetic rats (T2DR). The study was divided into acute phase (24 hours) and subacute phase (28 days). T2DR was induced by a combination of high-fat diet (HFD) and low-dose streptozotocin (STZ) (30 mg/kg). A dose of EKEE at 250 mg/kg was found to be most effective in lowering fasting blood glucose (FBS) in the acute study. The effect was further evaluated over 28 days in a sub-acute study. Thirty male Sprague-Dawley (SD) rats were divided into 4 groups. Group 1 – normal, Group 2 – untreated-diabetic rats, Group 3 – diabetic rats on EKEE (250 mg/kg) and Group 4 – diabetic rats on metformin (300 mg/kg). FBS, body weight, BMI and SBP were monitored biweekly. At the end of the study, renal function test, liver function test, lipid profiles, glucagon, and oxidative stress markers were evaluated. EKEE did not significantly reduce FBS. EKEE also did not prevent the reduction of body weight and BMI. Glucagon remains normal with EKEE. As for oxidative stress markers, EKEE significantly decreased MDA, and increased total antioxidative capacity, but not significant. These results suggested further study are needed to evaluate E. kingiana as an antidiabetic agent.